La muerte en la sierra de Piura: prácticas funerarias y creencias acerca de los muertos en las evidencias arqueológicas y en el material etnográfico - Polia, Mario (1997)
This essay aims to document the cultural continuity of funeral ritual ideas and practices among the peasant communities of the highland of Piura. Archaeological documents, colonial sources and ethnographic data allow an approach to traditional ideas about death and the spirits of the ancestors in the Andes of Piura. At the same time, they reveal not only the temporary survival of indigenous structures of religious thought, but the fundamental homogeneity of these structures throughout the Andean Peruvian and pan-American world. This article does not intend to extend the analysis to intercultural and interethnic comparisons: a topic, by the way, of relevant interest for both the archaeologist and the anthropologist.